Proceedings of the 12th annual deep brain stimulation think tank: cutting edge technology meets novel applications - Martinez-Nunez, Alfonso Enrique; Rozell, Christopher J.; Little, Simon; Tan, Huiling; Schmidt, Stephen L.; Grill, Warren M.; Pajic, Miroslav; Turner, Dennis A.; de Hemptinne, Coralie; Machado, Andre; Schiff, Nicholas D.; Holt-Becker, Abbey S.; et al. (Frontiers in Human Neuroscience, 2025)
The Deep Brain Stimulation (DBS) Think Tank XII was held on August 21st to 23rd. This year we showcased groundbreaking advancements in neuromodulation technology, focusing heavily on the novel uses of existing technology as well as next-generation technology. Our keynote speaker shared the vision of using neuro artificial intelligence to predict depression using brain electrophysiology. Innovative applications are currently being explored in stroke, disorders of consciousness, and sleep, while established treatments for movement disorders like Parkinson’s disease are being refined with adaptive stimulation. Neuromodulation is solidifying its role in treating psychiatric disorders such as depression and obsessive-compulsive disorder, particularly for patients with treatment-resistant symptoms. We estimate that 300,000 leads have been implanted to date for neurologic and neuropsychiatric indications. Magnetoencephalography has provided insights into the post-DBS physiological changes. The field is also critically examining the ethical implications of implants, considering the long-term impacts on clinicians, patients, and manufacturers.